The Effect of Internal and External Factors on SMEs Individual Taxpayer Non-compliance Behavior - Cahyani, Puspita Indah; Puspitosari, Indriyana (Journal of Business and Management Review, 2023)
This study aims to determine the variables of opportunity for non-compliance, costs of compliance, perceptions, and tax information on non-compliance by SMEs individual taxpayers. In this study, the SMEs individual taxpayer objects in the Surakarta area are used. This study analyzes the non-compliance factors of SMEs individual taxpayers in Surakarta. This study uses a quantitative approach. The type of data used is primary data obtained from the results of the questionnaire. The population in this study amounted to 17,965 SMEs. This study uses data from 100 respondents who meet the sample criteria. Data were analyzed using multiple regression analysis. The results showed that the variables of opportunity for non-compliance can increase tax non compliance behavior, cost of compliance and tax information reduce tax non-compliance behavior of SMES taxpayers in Surakarta.